The Time-Course of Changes in Muscle Mass, Architecture and Power During 6 Weeks of Plyometric Training - Monti, Elena; Franchi, Martino V.; Badiali, Francesca; Quinlan, Jonathan I.; Longo, Stefano; Narici, Marco V. (Frontiers in Physiology, 2020)
Purpose To investigate the time-course of changes in knee-extensors muscle mass, architecture and function in response to plyometric training (PLT) performed on a novel training device, the Tramp-Trainer. This machine consists in a trampoline connected to an inclined sledge which allows the performance of repeated jumps while the subject is sitting on a chair. Methods Eight healthy males (173.6 ± 4.7 cm, 69.7 ± 13.5 kg, 25.3 ± 4.6 years) underwent 6 weeks of bilateral PLT on the tramp-trainer machine. Training was performed three times per week (between 120 and 150 bounces per session). Knee-extensor maximum voluntary torque (MVT) and power, quadriceps femoris (QF) volume (VOL), cross-sectional area from the 20% to the 60% of femur length and CSAmean, together with vastus lateralis (VL) architecture (fascicle length, Lf, and pennation angle, PA) were assessed after 2, 4, and 6 weeks of PLT. Results All results are presented as changes versus baseline values. MVT increased by 17.8% (week 2, p < 0.001) and 22.2% (week 4, p < 0.01), respectively, and declined to 13.3% (p < 0.05) at week 6 of PLT. Power increased by 18.2% (week 4, p < 0.05) and 19.7% (week 6, p < 0.05). QF VOL increased by 4.7% (week 4, p < 0.05) and 5.8% (week 6, p < 0.01); VL VOL increased by 5.2%, (p < 0.05), 8.2%, (p < 0.01), and 9.6% (p < 0.05) at weeks 2, 4, and 6, respectively. An increase in Lf was detected already at wk 2 (2.2%, p < 0.05), with further increase at 4 and 6 weeks of PLT (4 and 4.4%, respectively, p < 0.01). PA increased by 5.8% (p < 0.05) at week 6. Significant positive correlations were found between CSAmean and Power (R2 = 0.46, p < 0.001) and between QF VOL and Power (R2 = 0.44, p < 0.024). Conclusions PLT induced rapid increases in muscle volume, fascicle length, pennation angle, torque and power in healthy younger adults. Notably, changes in VL VOL and Lf were detectable already after 2 weeks, followed by increases in knee extensors VOL and power from week 4 of PLT. Since the increase in CSAmean and QF VOL cannot fully explain the increment in muscle power, it is likely that other factors (such as adaptations in neural drive or tendon mechanical properties) may have contributed to such fucntional changes.